CHALLENGES AND SOLUTIONS OF ISLAMIC RELIGIOUS EDUCATION IN HIGH SCHOOL IN INDONESIA - Sya'bani, Mohammad Ahyan Yusuf (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Islamic Religious Education both in the sense of academic courses and as an institutional course has problems that need to be solved so that Islamic education in the future has an appeal and even makes a maximum contribution to students, college students, and the community in general. The challenges of globalization are currently making Islamic Education need to answer the readiness of its potential. Therefore, this study will elaborate on the challenges and solutions ofIslamic Religious Education as a discipline inuniversities both publicandprivateaswell as a variety of religiousunderstandings and ideologies that also in the practice of academic lifeincollege. The results ofthis study show several challenges and solutions for Islamic Religious Education in State Universities, Private Universities andfaith-based universities other than Islam, namely beban SKS which seems minimalist, pattern ofcontinuous learning, pattern of development of IslamicReligious Education, Dosen (Educator) of Islamic Religion, perilaku students who deviate from academic values, environment kampus, a new paradigm in the learning of Islamic Religious Education, the integration of Islamic inclusiveness in Islamic Religious Education, the Government's olithic particle towards Islamic Education in Indonesia, the lack ofreligious instruction hours, and the role ofIslamic Education in cultivate emotional intelligence.Meanwhile, the variety of Islamic religious understandings and ideologies in universities include the heterogeneity of institutions (structures) in charge of Islamic Religious Education on campus, the heterogeneity of the theme of the campus da'wah institute (LDK) study, the heterogeneity of extra-campus organizations, the heterogeneity of how students dress, and theheterogeneity of students' national views. All of them then affiliated with religious ideologies that developed a lot, especially in the context of Islamic Religious Education in universities, namelyNahdlatul Ulama, Muhammadiyah, Jama'ahTabligh, Muslim Brotherhood, Indonesian Islamic Da'wah Institute, and Salafi.